Does Help Seeking Behavior Change Over Time Following a Workplace Mental Health Intervention in the Coal Mining Industry?. Issue 6 (June 2019) - Sayers, Emma; Rich, Jane; Rahman, Md Mijanur; Kelly, Brian; James, Carole
Abstract : Objectives: To investigate help seeking behavior and attitudes to mental health in mining employees. Methods: A pre-post survey study of employees from two Australian coal mines. Data were collected prior to, at baseline, at 6 and 18 months following delivery of the MATES in mining (MIM) peer support mental health intervention. Results: Help seeking behaviors increased, with participants' sex, age, relationship status, shift type, and psychological distress significantly associated with likelihood of seeking help ( P <0.05). In relation to stigma, significantly more participants' disagreed that they would be treated differently by friends or colleagues following disclosure of mental illness ( P < 0.01). Conclusions: Results provide an understanding of help seeking behaviors of mining employees; support the MATES in Mining peer support program in the men dominated industry and provide information to guide mental health workplace program development more broadly.